The localization of androgen receptors in human bone. - Abu, E; Horner, A; Kusec, V; Triffitt, J; Compston, J (1997)
Androgens have important effects on the human skeleton, and deficiency has been associated with bone loss in both males and females. The skeletal actions of androgens may be mediated directly via the androgen receptor (AR) or indirectly via the estrogen receptor after aromatization to estrogens. The presence of androgen receptors has been demonstrated in bone cells and chondrocytes in vitro, but their presence in human bone in situ has not been reported. In order to provide further evidence for a direct action of androgens on bone via androgen receptors, we have used specific monoclonal antibodies to investigate the expression of human AR in normal developing and osteophytic bone of both sexes. In the growth plates from the developing bone, androgen receptors were predominantly expressed in hypertrophic chondrocytes and in osteoblasts at sites of bone formation. They were also observed in osteocytes in the bone, and in mononuclear cells and endothelial cells of blood vessels within the bone marrow. In the osteophytes, androgen receptors were widely distributed at sites of endochondral ossification in proliferating, mature, and hypertrophic chondrocytes and at sites of bone remodeling in osteoblasts. They were also expressed in osteocytes and mononuclear cells within the bone marrow. The pattern and number of cells expressing the receptor was similar in both sexes. Our results show for the first time the presence and distribution of androgen receptors in normal developing human and osteophytic bone in situ and further provide evidence for a direct action of androgens on bone and cartilage cells.